ANALISIS KEBIJAKAN DIVIDEN PADA PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - admin, Annisa Wijaya B1021131022 (Jurnal Manajemen Update, 2017)
This research aims to obtain empirical evidence about the analysis dividend policy for property and real estate companies sector listed on Indonesia Stock Exchange. The dependent variable used is the dividend policy, whereas the independent variables used are profitability, liquidity, leverage, size, and growth earning. The type of this research was quantitative research by taking secondary data. Sampling technique was collected by purposive sampling with total 34 property and real estate companies listed on Indonesia Stock Exchange in period of 2011 – 2015. The results of this research showed that cash position had a positive significantly effect to dividend policy. As for profitability, leverage, size, and growth earning had no significantly effect to dividend policy. Keywords : Return on Equity, Cash Position, Debt to Equity Ratio, Size, Growth Earning, Dividend Payout Policy